Petal senescence: a hormone view. (6th February 2018) - Ma, Nan; Ma, Chao; Liu, Yang; Shahid, Muhammad Owais; Wang, Chengpeng; Gao, Junping
Abstract : This review specifically focuses on recent progress in hormonal regulation of flower senescence. . Abstract: Flowers are highly complex organs that have evolved to enhance the reproductive success of angiosperms. As a key component of flowers, petals play a vital role in attracting pollinators and ensuring successful pollination. Having fulfilled this function, petals senesce through a process that involves many physiological and biochemical changes that also occur during leaf senescence. However, petal senescence is distinct, due to the abundance of secondary metabolites in petals and the fact that petal senescence is irreversible. Various phytohormones are involved in regulating petal senescence, and are thought to act both synergistically and antagonistically. In this regard, there appears to be developmental point during which such regulatory signals are sensed and senescence is initiated. Here, we review current understanding of petal senescence, and discuss associated regulatory mechanisms involving hormone interactions and epigenetic regulation.